2012
DOI: 10.1016/j.adolescence.2012.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Brief report: Improving the validity of assessments of adolescents' feelings of privacy invasion

Abstract: Studies of privacy invasion have relied on measures that combine items assessing adolescents' feelings of privacy invasion with items assessing parents' monitoring behaviors. Removing items assessing parents' monitoring behaviors may improve the validity of assessments of privacy invasion. Data were collected from 163 adolescents (M age 13 years, 5 months; 47% female; 50% European American, non‐Hispanic, 46% African American) and their mothers. A model specifying separate factors for privacy invasion and monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…Adolescents responded to six items assessing feeling of privacy invasion (e.g., “My parents invade my privacy”) adapted from Hawk, Hale, Raaijmakers, and Meeus (). We excluded items assessing parental monitoring behavior from the feelings of privacy invasion measure (see Laird, Marrero, Melching, & Khun, , for rationale and further discussion). Responses to both sets of items were scored using a 5‐point scale (0 = strongly disagree , 1 = disagree , 2 = agree nor disagree , 3 = agree , 4 = strongly agree ).…”
Section: Methodsmentioning
confidence: 99%
“…Adolescents responded to six items assessing feeling of privacy invasion (e.g., “My parents invade my privacy”) adapted from Hawk, Hale, Raaijmakers, and Meeus (). We excluded items assessing parental monitoring behavior from the feelings of privacy invasion measure (see Laird, Marrero, Melching, & Khun, , for rationale and further discussion). Responses to both sets of items were scored using a 5‐point scale (0 = strongly disagree , 1 = disagree , 2 = agree nor disagree , 3 = agree , 4 = strongly agree ).…”
Section: Methodsmentioning
confidence: 99%
“…A Dutch translation of the Level of Expressed Emotion (LEE) questionnaire (Hale, Raaijmakers, Gerlsma, & Meeus, 2007) assessed adolescents' perceptions of privacy invasion. A recent study (Laird, Marrero, Melching, & Kuhn, 2013b) recommended omitting three items of the original seven-item measure to avoid conflating perceived invasion with perceived monitoring. Adolescents responded to four items on a 5-point scale (1 = strongly disagree; 5 = strongly agree).…”
Section: Methodsmentioning
confidence: 99%
“…Although there is growing knowledge about parental monitoring in cyberaggression, much less is known about the role of youth disclosure. Early adolescents are reluctant to disclose information to their parents (Laird et al, 2013). Makri-Botsari and Karagianni (2014) indicated that the majority of adolescents in their study preferred to report cyberaggression incidents to their friends rather than to their parents.…”
Section: Parental Monitoringmentioning
confidence: 95%
“…They begin to take control over the amount of information they share with their parents by not revealing thoughts and experiences as freely as in the past (Frijns et al, 2020). In an attempt to regain control, parents may monitor or restrict the adolescent's activities, or explicitly solicit information from them (Laird et al, 2013).…”
Section: Parental Monitoringmentioning
confidence: 99%